The Effectiveness of Virgin Coconut Oil (VCO) and Sunflower Oil on Striae Gravidarum of Second Trimester Pregnancy in Public Health Centre of Tumpaan Manado, North Sulawesi - Sjeny Olga Tuju; Fredrika Nancy Losu; Sandra G. J. Tombokan; Jovie Mien Dumanauw; Freike S. N. Lumy; Atik Purwandari; Fonnie Kuhu; Els Ivy Kulas; Martha D. Korompis; Muhamad Ali Makaminan; Wahyuni Wahyuni; Viviane Tangkuman (Aloha International Journal of Health Advancement (AIJHA), 2021)
Striae Gravidarum can be prevented by giving virgin coconut oil which is pure oil by farmers specifically for the province of North Sulawesi, which is the main product of coconut raw materials containing lauric acid and oleic acid which are effective in maintaining skin elasticity. Sunflower Oil developed without going through genetic engineering from plants contain more linoleic acid than oleic acid. The purpose of the study was to determine the effect of giving oil on the incidence of striae gravidarum in pregnant women. Method: analytical research design quasi-experimental approach pre-posttest design with two groups. Samples were all primigravida pregnant women with gestational age of 20-28 weeks as many as 50 samples consisting of 25 respondents were given VCO and 25 respondents were given Sunflower Oil. Bivariate data analysis with t-independent pairet test. The results of this study applying VCO with an average amount of 136.1 ml, there was a difference in the pairet test test(p=0.000) giving sunflower oil before and after applying sunflower oil on average as much as 128 ml there was a difference before and after being given sunflower oil(p= 0.008) The conclusion is there is a difference before and after applying VCO and Sunflower Oil. Keywords: virgin coconut oil (VCO); striae gravidarum; pregnant women